HYDROLYSIS DEGREE OF THE HYDROLYSATE PROTEIN FROMBIVALVE (Anadara antiquata) USING BROMELIN ENZYME AT DIFFERENT CONCENTRATIONS - Sholihah, Aulia Putri; Edison, Edison; Karnila, Rahman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT            Bivalve Anadara antiquatameat has a potential use as a raw material for producing protein hydrolyzate because it contains quite high protein.However, it has not been utilized optimally in its processing, so that it is necessary to do research on producing protein hydrolyzate fromthe bivalve with the addition of bromelin enzymes. It is hoped that it will provide the opportunity as an alternative source of animale protein and will increase the added value of the bivalve. The purpose of this study was to produce protein hydrolyzate from the bivalve using the bromelin enzyme. The method use was experimental composed as a non-factorial completely randomized design. It was contained 4 treatment levels of different enzyme concentrations(0%, 3%, 6%, and 9%). Parameters observed were the yield and the degree of hydrolysis. The addition of Bromelin enzyme at different concentrations has a very significant effect on the yield value and the hydrolysis degree. The addition of 9% enzyme was the best treatment. The best yield value on the hydrolyzate protein of bivalve after freeze drying15.62% and the value of the degree of hydrolysis was 14.68% and was the optimum condition for hydrolyzing bivalve meat.Keywords: Bivalve, Bromelin Enzyme, HydrolyzateProtein